Development of DISCA (Digital Smart Card) Learning Media Based on Critical Thinking for Energy Conversion Material in Grade IV Elementary School - Kasanah, Uswantun; Utama, Candra; Thohir, Muhammad Anas (Proceedings Series of Educational Studies, 2024)
The purpose of this research is to create a critical thinking-based instructional media called DISCA (Digital Smart Card) for energy conversion materials that is valid according to subject matter experts, media experts, teachers, practical according to students, and effective in stimulating students' critical thinking skills. This R&D process employs the ADDIE model. The critical thinking-based DISCA refers to Facione with indicators adapted to Piaget's cognitive development for fourth-grade elementary school, which include analysis, evaluation, and explanation. The results showed that the product received average percentage of 93.75% indicating a "very valid" category. In practicality with average percentage of 98.8% categorized as "very practical." The effectiveness in stimulating critical thinking skills using the N-Gain Score showed that it was with a score of 80,19% indicating an “effective”. These research, it can be concluded that the DISCA for energy conversion materials for fourth-grade elementary school students is considered very valid, considered very practical, effective in stimulating critical thinking. Keywords: Learning Media, Digital Smart Card Critical Thinking Skills, Energy Conversion